2020
DOI: 10.1186/s40364-020-00239-8
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated bile acid receptor-mediated signaling and IL-17A induction are implicated in diet-associated hepatic health and cognitive function

Abstract: Background Chronic consumption of high sugar and high fat diet associated with liver inflammation and cognitive decline. This paper tests a hypothesis that the development and resolution of diet-induced nonalcoholic fatty liver disease (NAFLD) has an impact on neuroplasticity and cognition. Methods C57BL/6 wild-type mice were fed with either a healthy control diet (CD) or a fructose, palmitate, and cholesterol (FPC)-enriched diet sin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 67 publications
1
34
0
Order By: Relevance
“…An increasing number of experimental studies have shown evidence of cognitive dysfunction and neuroinflammation in animal models of NASH. Collectively, these studies indicate that NASH is associated with impaired spatial learning and memory as well as depression-like behaviour, and that these neurobehavioral changes are accompanied by microglia activation and increased release of proinflammatory cytokines in brain tissue [ 61 , 62 , 63 ]. Furthermore, the induction of NAFLD in models of Alzheimer’s disease (AD) and haemorrhagic brain injury exacerbates cognitive impairment and neuroinflammation [ 64 , 65 ].…”
Section: Possible Mechanisms Behind Cognitive Dysfunction In Nafldmentioning
confidence: 99%
“…An increasing number of experimental studies have shown evidence of cognitive dysfunction and neuroinflammation in animal models of NASH. Collectively, these studies indicate that NASH is associated with impaired spatial learning and memory as well as depression-like behaviour, and that these neurobehavioral changes are accompanied by microglia activation and increased release of proinflammatory cytokines in brain tissue [ 61 , 62 , 63 ]. Furthermore, the induction of NAFLD in models of Alzheimer’s disease (AD) and haemorrhagic brain injury exacerbates cognitive impairment and neuroinflammation [ 64 , 65 ].…”
Section: Possible Mechanisms Behind Cognitive Dysfunction In Nafldmentioning
confidence: 99%
“…In addition, BAs also modulate GABAergic and N-methyl-D-aspartate receptor-mediated neurotransmission [70]. Our previous data showed that fructose-enriched WD induced gut and brain inflammation [2,34]. Moreover, reducing BA pool size effectively reduces skin inflammation and liver damage [71][72][73].…”
Section: Discussionmentioning
confidence: 99%
“…Untargeted, semi-quantitative metabolomics profiling was performed using cecal metabolites. Gas chromatography time of flight mass spectrometry was conducted at the UC Davis West Coast Metabolomics Center based on published methods [30,33,34]. BinBase database was used to process acquired spectra, filtered, and matched with the Fiehn mass spectral library of 1200 authentic metabolite spectra with retention index and mass spectrum information or against the NIST library.…”
Section: Untargeted Metabolomics Profilementioning
confidence: 99%
See 1 more Smart Citation
“…Notably, ReHo values in the LAG were positively associated with the RA of Coprobacter in our study. Genus Coprobacter has been found to be positively associated with insulin supplementation ( Jena et al, 2020 ), an indigestible fiber that can generate short-chain fatty acids ( Weitkunat et al, 2015 ) and improve digestion, memory, and mood in humans ( Smith et al, 2015 ). Our results showed that the RA of this bacteria was positively correlated with better cognitive performance in CI patients, which may indicate potential benefits of this gut bacteria.…”
Section: Discussionmentioning
confidence: 99%